MAKING OF NATURAL ZEOLITES AS STONE CERAMICS AT TEMPERATURE OF LESS THAN 1000OC - Fatimah, Dewi (Jurnal Zeolit Indonesia, 2006)
Nowadays, ceramics world has been developing into what the interior, building exterior, industries and household. The quality and its ability made by certain specification which compatible with the structure, design and the function. For example, the building structure that usually has high humidity whether indoor or outdoor will need certain ceramics for the floor to keep on dry condition, unslippery, clean while fungus will not live. For that purpose stone ceramics that made by natural zeolite will has same characters as natural zeolite function such us absorb/release water reversibly, absorb smelt or volatile compound, molecular filter. The making of zeolite ceramic was done at certain burning temperature where natural structure of zeolite will not be destructed or collaps and forming amorphous compound. So the natural zeolite function will preserve. The development of composite is made from natural zeolite as the main ingredients which clay, kaolin, and feldspar are used as binders. In order to decrease burning temperature, natrium compound added into the composite and the experiment done at temperature 800-1000 oC with composite pressure between 50-100 kg/cm. the result of experiment indicate that on burning temperature 800oC whether with using SEM or XRD analysis, zeolite is in mordenite crystal form. Whereas at burning temperature 1000oC, the crystal structure of zeolite has been destructed and forming albit and calcian as new compound. The zeolite ceramics which formed at 800 oC, with pressure at 50 kg/cm has strong and compact characters with absorption ability up to 23%.